Choctaw Confederates : The American Civil War in Indian Country - Yarbrough, Fay A. (Book collections on Project MUSE., 2021)
"When the Choctaw Nation was forcibly resettled in Indian Territory in present-day Oklahoma in the 1830s, it was joined by enslaved Black people-the tribe had owned enslaved Blacks since the 1720s. By the eve of the Civil War, 14 percent of the Choctaw Nation consisted of enslaved Blacks. Avid supporters of the Confederate States of America, the Nation passed a measure requiring all whites living in its territory to swear allegiance to the Confederacy and deemed any criticism of it or its army treasonous and punishable by death. Choctaws also raised an infantry force and a cavalry to fight alongside Confederate forces. In Choctaw Confederates, Fay Yarbrough reveals that, while sovereignty and states' rights mattered to Choctaw leaders, the survival of slavery was what determined the Nation's support of the Confederacy"--